Clinical characteristics of patients with benign nonlesional temporal lobe epilepsy - Kim J (Dove Medical Press, 2016)
Jiyeon Kim,1 Seong Hoon Kim,2 Sung Chul Lim,2 Woojun Kim,2 Young-Min Shon3 1Department of Neurology, Korea University Ansan Hospital, College of Medicine, Korea University, Ansan, 2Department of Neurology, Catholic Neuroscience Institute, College of Medicine, The Catholic University of Korea, Seocho-gu, 3Department of Neurology, Samsung Medical Center, Sungkyunkwan University School of Medicine, Seoul, Korea Purpose: To evaluate the evolution of nonlesional temporal lobe epilepsy (TLE-NL) in patients treated exclusively with antiepileptic drugs and to elucidate clinical phenotypes related to the prognosis of these patients.Methods: Clinical, radiological, and electroencephalographic (EEG) findings in 84 patients with TLE-NL were reviewed. A good response group (GRG) and a poor response group (PRG) were defined if the duration of their seizure-free period was >1 year, or <1 year, respectively.Results: There were 46 (54.8%) patients in the GRG and 38 (45.2%) patients in the PRG. The number of antiepileptic drugs administered was significantly lower in the GRG than that in the PRG (1.3±0.8 vs 2.8±1.0, respectively; P<0.05). The GRG had a significantly older age of onset than the PRG and a lower occurrence of initial precipitating events, such as febrile seizures, central nervous system infection, and head trauma (P<0.05). The prevalence of EEG abnormality, presence of aura, generalized seizures, and automatism was less frequently observed in the GRG (P<0.05). Multivariate analysis showed that the presence of automatism and initial precipitating events were significantly associated with a poor prognosis (P<0.05).Conclusion: In contrast to the commonly assumed intractability of TLE, we found that more than 54% of patients with TLE-NL achieved a long seizure-free period. Older age at onset of TLE-NL was associated with a better prognosis. However, the presence of automatism and initial precipitating events were related to a poor prognosis. Future prospective studies with a much larger population are warranted. Keywords: epilepsy, benign temporal lobe epilepsy, nonlesional temporal lobe epilepsy